Speaking the language of the kingdom of God in the context of a society in transition - Wet, FriedrichW. de (HTS teologiese studies, 2010)
Venturing to speak the biblical language of the kingdom of God, with its distinct covenantal intensity, in the context of a South African society in transition from paternalistic power structures to liberal democratic structures is not easy. How should the language of the kingdom of God be spoken in a society that demands ‘non-intrusive’ and ‘politically correct’ speech without – in the process – rendering the intense intentionality of its covenantal roots to that of a speech without zeal? Having to face the daunting task of ‘translating’ kingdom language into a type of language that suits the present-day context without sacrificing or diminishing its powerful intentionality demands the development of a new sensitivity. Such a sensitivity is required to incentivise the accommodation of the dimensions of truthful, authoritative and authentic communication in spoken language. In this research article, the implications of the speech act theory, as pioneered by scholars such as J.L. Austin and J. Searle, are utilised to identify possible markers for such a venture. Insight into the locutionary, illocutionary and perlocutionary dimensions present in speech acts is indicated as a relevant starting point for attempting to obtain a more comprehensive and perspective-rich understanding into speaking the language of the kingdom of God in a way that fits the present South African context.